A System Interface Design of Free Open Resource for Geospatial Data and Software (FORGeDS): A Spatial Data and Tools Cloud Storage Application - Rachmadhi, Adzanil Rachmadhi Putra; Anaking, Purnama; Ramdani, Fatwa (Journal of Education Technology and Information System, 2025)
Geospatial data is an essential element in areas such as spatial planning, natural resource management, disaster mitigation, and transportation planning. However, managing this data requires specialized software, such as QGIS and ArcGIS, which operate offline and do not include the required spatial data directly. The process of acquiring geospatial data, whether through field surveys or accessing online platforms, is often time-consuming and not always as specific as needed. One of the platforms that provide geospatial data in Indonesia is the Geospatial Information Agency (BIG), but complicated access procedures are often a barrier for users This study aims to design FORGEDS (Free Open Resource for Geospatial Data and Software), an open-source portal that provides geospatial data and tools that can be accessed easily without going through a complicated login process. Using a Human-Centered Design (HCD) approach with the PACT Framework (People, Activities, Contexts, Technologies), the system is designed to provide an intuitive and efficient user experience. FORGEDS is also built with CSS Bootstrap Framework and Laravel Framework to ensure responsive interface and feature development flexibility. FORGEDS is expected to be an inclusive and efficient solution in the utilization of geospatial data, as well as encourage the use of open-source technology in the wider community.